2018
DOI: 10.1097/cpt.0000000000000083
|View full text |Cite
|
Sign up to set email alerts
|

Body Position Affects Ultrasonographic Measurement of Diaphragm Contractility

Abstract: Purpose:(1) Determine whether ultrasonography can detect differences in diaphragm contractility between body positions. (2) Perform reliability analysis of diaphragm thickness measurements in each test condition.Methods:We used a repeated-measures experimental design with 45 healthy adults where 3 B-mode ultrasound images were collected at peak-inspiration and end-expiration in supine, sitting, and standing. Mean diaphragm thickening fractions were calculated for each test position. Statistical significance wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Thus, the cutaneous landmark positioned would indicate pleural plane in a point very different from that evaluated by ultrasound, when the patient assumes a supine position for HRCT scans. It is known that changing posture, the position of the diaphragm, motility and lung volumes dramatically change as well [27][28][29][30]. Also, the position of arms affects diaphragm height, and consequently the position of the lung [31].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the cutaneous landmark positioned would indicate pleural plane in a point very different from that evaluated by ultrasound, when the patient assumes a supine position for HRCT scans. It is known that changing posture, the position of the diaphragm, motility and lung volumes dramatically change as well [27][28][29][30]. Also, the position of arms affects diaphragm height, and consequently the position of the lung [31].…”
Section: Discussionmentioning
confidence: 99%
“…Low TF was a good predictor of weaning outcome with consistency across studies, and higher dOR suggests that TF has better diagnostic accuracy than DE. Both TF and DE are reproducible [196,198,[200][201][202][203][204]. However, in a large multicentre randomised controlled trial by VIVIER et al [205], diaphragmatic dysfunction identified by TUS was not associated with an increased risk of extubation failure.…”
Section: Diaphragmmentioning
confidence: 99%
“…Moreover, patient position may affect respiratory function tests [28]. Here, with US, patients were in a semirecumbent position (45°) that would amplify diaphragm dysfunction and US measurements [27, 29]. The supine position is preferred, because there is less overall variability, less side-to-side variability, and greater reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…The supine position also exaggerates any paradoxical movement and limits any compensatory active expiration by the anterior abdominal wall, which may mask paralysis [4]. According to Brown et al [29], intraobserver reliability was excellent (>0.93) for all body positions tested. Because many of our patients were not able to maintain the strict supine position for different reasons (e.g., tolerability), we systematically used the semirecumbent position (45°).…”
Section: Discussionmentioning
confidence: 99%